“Emas non quod opus est, sed quod necesse est?” Soldiers’ Pay and its Purchasing Power in the Byzantine Army in the 9th-10th Centuries - Wierzbiński, Szymon (Vox Patrum, 2026)
The issue of the earnings of Byzantine soldiers is one of the most frequently discussed topics. A topic that still raises controversy is the financial situation of thematic soldiers, who are often omitted in available sources. The aim of this text is an attempt to determine the amount of earnings and purchasing power of thematic soldiers in the period of the 9th - 10th centuries. The analysis consists in confrontation of sources and a response to the current state of research. The main conclusion of the text is that the financial situation of theme soldiers was varied and depended on whether the recruit derived his main income from the soldiers' land or was a volunteer with no better prospects for life. In the latter case, only the veteran status allowed one to achieve income sufficient to support a family.